Numerical and experimental analysis of heat transfer and nanofluid flow through an annular pipe with abrupt contraction - Abdulrazzaq, Tuqa (2015)
The energy crises in the worldwide have been encouraging the researchers to look for new methods which increase of thermal performance. One of common technique to improve efficiency of energy system equipment is by changing the design configuration of channel and conventional fluid such as nanofluids. Enhancements of heat transfer and nanofluid flows through an annular channel with abrupt contraction are numerically and experimentally investigate. The finite volume method in three dimensional domains with an SST K-ω model is use in simulation. Aluminum oxide and titanium oxide (Al2O3, TiO2) nanoparticles with volume fractions varied from 0.5% to 2% have been use. Reynolds number range varying between 10000 and 40000 and contraction ratios from 1 to 2 at heat flux varied from 1000 W/m2 to 6000 W/m2 were apply. In order to validate numerical results Al2O3 water based nanofluid was use in experimental study. The outer cylinder of the entrance pipe had a constant diameter while the outer cylinder of the exit pipe had different diameters to generate the contraction. Both the entrance and exit pipe were heated under uniform heat flux and the overall length of the inner cylinder were unheated and has constant diameter. The results showed that the maximum heat transfer coefficient was about 194.7% in an annular pipe with contraction ratio of 2 compared with a straight pipe, due to the generated recirculation flow zone that begins after the separation point of the wall. It was observed that by increasing nanoparticle volume fraction for all type of nanofluids, enhances the heat transfer coefficient due to augmented heat transport by nanoparticles in base fluid which raises the convection heat transfer where were about 26.9 % ( Al2O3) and 5.5% (TiO2). Also the effect of Reynolds number on the increase of surface heat transfer coefficient noted. Recirculation regions appeared to increase with increasing step height and Reynolds number. Also pressure drop observed decreases and increases before and after the step due to recirculation flow. The maximum pressure drop were about 7.5% (Al2O3) and 5.9% (TiO2) nanofluid compared with pure water at contraction ratio of 2 and Reynolds number of 40000. Additional investigations have been done in this research in order to clarify the effect of separation flow on augmentation of heat transfer and pressure drop. Heat transfer and turbulent fluid flow over double forward-facing step or through annular pipe with sudden contraction were performed numerically. Same findings have been observed in those studies where increase of thermal performance and pressure drop with increases Reynolds number and step heights.